Hành vi sử dụng dịch vụ giao đồ ăn trực tuyến của khách hàng Việt Nam trong thời kỳ dịch bệnh COVID-19 - Nguyễn Thị Mỹ , Nguyệt; Nguyễn Hoàng , Việt; Vũ Tuấn , Dương (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
The aim of this study is to analyse the intention and behavior of Vietnamese consumers in using online food delivery (OFD) services based on Protection Motivation Theory (PMT) and Technology Acceptance Model (TAM) and to look for evidence of differences in age groups (generation Y and generation Z) of customers when using the service during the pandemic crisis. The results illustrated that perceived the pandemic’s severity, perceived benefits, and perceived ease of use of the OFD services have a positive impact on the intention of Vietnamese customers toward this type of service. Furthermore, we find that the 18-25 age group’s purchase intention is more influenced by the perception of the epidemic severity and the perceived easy usage of the service, while the intention of use of the age group of 26-40 is a better predictor of behavior of use than the customer group aged from 18 to 25. We provide recommendations for online delivery service companies to address customer’s purchase motives and during an epidemic crisis.
Keywords: COVID-19; Online food delivery; Intension of use; Usage behavior; Generation Y; Generation Z